Advisor Appointment & Follow-up System for ITDI Faculty - บำรุงเอื้อ, ปทุม; คงชอบ, ดุษิต; คล่องรักสัตย์, เกรียงไกร; ส่วยสิน, พัชรินทร์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to (1) analyze user requirements and design a web-based appointment scheduling and academic advising follow-up system aligned with the operational context of the Faculty of Information Technology and Innovation, (2) develop a system with core functionalities including online booking, schedule management, advising record documentation, and systematic follow-up, and (3) evaluate the system’s effectiveness in reducing procedural steps and processing time, improving data accuracy, and enhancing user satisfaction. The research employed a quasi-experimental design. The sample consisted of three information technology experts and fifteen system users, selected through purposive sampling. The research instruments included the developed web-based system, an expert evaluation form, and a user satisfaction questionnaire. Data were analyzed using descriptive statistics, including mean and standard deviation.           The findings revealed that the developed system functioned effectively according to its designed specifications, featuring real-time updates and centralized data management. Expert evaluation indicated that overall system efficiency was at the highest level (M = 4.76, SD = 0.22), particularly in functional performance and system security. User evaluation also demonstrated the highest level of satisfaction (M = 4.75, SD = 0.38), with the highest-rated aspect being the system’s ability to reduce procedural complexity and save time (M = 4.87, SD = 0.35).           In conclusion, the development of the appointment scheduling and academic advising follow-up system significantly enhanced process efficiency, reduced redundancy, improved data accuracy, and achieved a high level of user satisfaction. The system provides a foundational mechanism for proactive advising and data-driven management, ultimately supporting long-term student success.